The effects of metabolic status on non‐alcoholic fatty liver disease‐related outcomes, beyond the presence of obesity. Issue 11 (23rd October 2018) - Ampuero, Javier; Aller, Rocío; Gallego‐Durán, Rocío; Banales, Jesus M.; Crespo, Javier; García‐Monzón, Carmelo; Pareja, María Jesús; Vilar‐Gómez, Eduardo; Caballería, Juan; Escudero‐García, Desamparados; Gomez‐Camarero, Judith; Calleja, José Luis; et al.
Summary: Background: Metabolically healthy obesity (MHO) shows a reduced risk compared with obese patients with adverse metabolic conditions. Lean people suffering some metabolic derangements also have non‐alcoholic fatty liver disease (NAFLD)‐related outcomes compared with non‐obese subjects with a few metabolic risks. Aim: To define the impact of the metabolic status on the NAFLD‐related outcomes, beyond the presence of obesity. Methods: We designed a multicentre cross‐sectional study, including 1058 biopsy‐proven NAFLD patients. Metabolically healthy status was strictly defined by the lack of metabolic risk factors (diabetes mellitus, low HDL, hypertriglyceridemia, arterial hypertension). Non‐alcoholic steatohepatitis (NASH) and significant fibrosis (F2‐F4) were identified by liver biopsy. Chronic kidney disease epidemiology collaboration equation was calculated for kidney function and the atherogenic index of plasma (AIP) for cardiovascular risk. Results: Metabolically healthy (OR 1.88; P = 0.050) and unhealthy obesity (OR 3.47: P < 0.0001), and unhealthy non‐obesity (OR 3.70; P < 0.0001) were independently associated with NASH together with homeostatic model assessment (HOMA), ALT, and platelets. Significant fibrosis was more frequently observed in the presence of adverse metabolic conditions in obese (OR 3.89; P = 0.003) and non‐obese patients (OR 3.92; P = 0.002), and independently associated with platelets, albumin, ALT, HOMA, and age. The number of metabolic factors determined the risk of NASH and significant fibrosis. Glomerular filtration rate was lower in unhealthy (91.7 ± 18) than healthy metabolism (95.6 ± 17) ( P = 0.007). AIP was higher in adverse metabolic conditions ( P = 0.0001). Metabolically unhealthy non‐obesity showed higher liver damage (NASH 55.8% vs 42.4%; P < 0.05; significant fibrosis 31.7% vs 11.4%; P < 0.0001) and cardiovascular risk ( P < 0.0001) than healthy obesity. Conclusions: Metabolic unhealthy status showed a greater impact on NASH, significant fibrosis, kidney dysfunction, and atherogenic profile than obesity. However, metabolically healthy obesity was not a full healthy condition. We should focus our messages especially on patients with adverse metabolic conditions.